THE EFFECT OF TRAINING, COMPETENCE, AND WORK MOTIVATION TOWARD EMPLOYEES PERFORMANCE AT HEAD OFFICE OF PT. BANK SULTENG - Feby, Feby; Idris, Idris; Darman, Darman (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2021)
This research intends to analyze the effect of training, competence and work motivation toward employees performance at PT. Central Sulawesi Bank. This is descriptive-verificative research. The data obtained were analyzed through Multiple Linear Regression analysis. Respondents involved were 65 permanent employees who have attended training. The results show that training, competence and motivation simultaneously had a significant effect on employee performance at Head Office PT. Bank Sulteng with an Adjusted R Square value of 34.2%. Partially, training has a positive effect but not significant to employee performance at PT. Bank Sulteng Head Office, competence has a positive and significant effect on employee performance at Head Office PT. Central Sulawesi Bank and motivation have a positive effect but not significant on employee performance at Head Office PT. Bank Sulteng. Keywords: Training, Competence, Work Motivation, Employee Performance